Website Utilization as Labuan Bajo Super Digital Marketing - Saleh, M. Surya; Nugraha, Rizki Nurul (West Science Social and Humanities Studies, 2024)
Digital marketing by utilizing websites can have a significant impact, such as improving their brand image, reaching a wider audience, and expanding the target market. The purpose of this study is to identify the website as Labuan Bajo Super's digital marketing tool. This type of research is qualitative, with qualitative descriptive analysis methods. Data collection was carried out by observing the Labuan Bajo Super website and taking the necessary data in this study. The result of the study is Labuan Bajo Super making good use of the website as their marketing medium. Labuan Bajo Super provides complete information, such as displaying information on tour packages offered, Labuan Bajo Super contact information, and more.